Control of spin-wave transmission by a programmable domain wall. Issue 1 (December 2018) - Hämäläinen, Sampo; Madami, Marco; Qin, Huajun; Gubbiotti, Gianluca; van Dijken, Sebastiaan
Abstract Active manipulation of spin waves is essential for the development of magnon-based technologies. Here, we demonstrate programmable spin-wave filtering by resetting the spin structure of pinned 90° Néel domain walls in a continuous CoFeB film with abrupt rotations of uniaxial magnetic anisotropy. Using micro-focused Brillouin light scattering and micromagnetic simulations, we show that broad 90° head-to-head or tail-to-tail magnetic domain walls are transparent to spin waves over a broad frequency range. In contrast, magnetic switching to a 90° head-to-tail configuration produces much narrower and strongly reflecting domain walls at the same pinning locations. Based on these results, we propose a magnetic spin-wave valve with two parallel domain walls. Switching the spin-wave valve from an open to a closed state changes the transmission of spin waves from nearly 100 to 0%. Active control over spin-wave transport through programmable domain walls could be utilized in magnonic logic devices or non-volatile memory elements. Magnon-based spintronic devices crucially rely on the capability of spin wave manipulation. Here the authors achieve active control of spin wave transmission by programming a pinned 90 degree Néel domain wall in a continuous CoFeB/BaTiO3 film with abrupt rotations of uniaxial magnetic anisotropy.